Management of Congenital Talipes Equino Varus (CTEV) by Ponseti Casting Technique - Karn, Navin; Jha, Ranjib; Gupta, Yogendra (Nepal Orthopaedic Association Journal, 2019)
OBJECTIVE: The purpose of this study is to evaluate the results of Ponseti technique in the management of Congenital Talipes Equino Varus (CTEV) in children. METHODS: It is a prospective observational study, conducted during the period of January 2012 to December 2014 atthe Department of Orthopedics Nobel Medical College Teaching Hospital. All the patients with CTEV were treated with Ponseti casting technique.The children with clubfeet associated with meningocele, meningomyelocele, arthrogryposis multiplex congenita and other neuromuscular causes were excluded. RESULTS: Sixty feet in 38 patients, 22 with bilateral and 16 with unilateral clubfeet in children less than two years of age and without any prior manipulation or surgical treatment were selected for Ponseti methods of manipulation. 26 were males and 12 were females. Thirty seven (61.66%) feet were of rigid variety and twenty three (38.83 %) feet were of non-rigid variety. Mean pre-treatment Pirani score of study group was 5.57. Mean number of plaster casts required per CTEV was 5 (range:3-6). Thirty seven rigid and fifteen non-rigid total 52(86.66%) feet required percutaneous tenotomy. Out of 60 feet 58 (96.6%) were managed successfully. Two (3.33%) patients developed complications like blister formation. Mean post-treatment Pirani score of the study group was 0.36 ± 0.43. CONCLUSION: The Ponseti technique is an excellent, simple, effective, minimally invasive, and inexpensive procedure for the treatment CTEV deformity. Ideally it can be performed as a day care procedure without general anesthesia.